Preliminary analysis of a soft-storey mechanism after the 2009 L'Aquila earthquake. - Verderame, Gerardo M. (Earthquake engineering & structural dynamics.)
Observation of damage caused by the recent Abruzzo earthquake on April 6th 2009 showed how local interaction between infills and RC structures can lead to soft-storey mechanisms and brittle collapses. Results of the present case study are based on observed damage caused by the earthquake in the zone of Pettino. Analytical model based on simulated design procedure was built up and time history analyses were employed to verify the causes of the structural collapse, as highlighted by observed damage. This failure mechanism was investigated taking into consideration all components of the ground motion. Nonlinear behavior of brick masonry infills was taken into account and two parametric hypotheses for infill mechanical properties were considered, given the uncertainties that typically characterize these nonstructural elements. Nonlinear modeling of infills was made by a three-strut macro-model aimed at considering both local and global interaction between RC frame and infills. Seismic input was characterized by the real signal registered during the mainshock near the case study structure. Different shear capacity models were considered in the assessment. Analytical results seem to confirm with good approximation the likely collapse scenario that damage observation highlighted; the lack of proper detailing in the columns made the local interaction between infills the RC columns and the strong vertical component of the ground motion to be the main causes of the brittle failure.